Responsibility of the psychological professional activity - S V Bykov; S A Gavrilushkin (Peoples' Friendship University of Russia (RUDN University), 2011)
The article gives a keen study of the term moral responsibility and shows the importance of this phenomenon for the professional activity of the psychologist.